Music, Liturgy, and Confraternity Devotions in Paris and Tournai, 1300-1550 - Long, Sarah Ann (Eastman studies in music., 2021)
The first study focusing on the composition of new plainchant in northern-French confraternities for masses and offices in honor of saints thought to have healing powers.